2014
DOI: 10.1093/mnras/stu2363
|View full text |Cite
|
Sign up to set email alerts
|

On the radio properties of the intermediate-mass black hole candidate ESO 243-49 HLX-1

Abstract: We present follow-up radio observations of ESO 243-49 HLX-1 from 2012 using the Australia Telescope Compact Array (ATCA) and the Karl G. Jansky Very Large Array (VLA). We report the detection of radio emission at the location of HLX-1 during its hard X-ray state using the ATCA. Assuming that the 'Fundamental Plane' of accreting black holes is applicable, we provide an independent estimate of the black hole mass of M BH 2.86 M ⊙ at 90% confidence. However, we argue that the detected radio emission is likely to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 90 publications
1
42
0
Order By: Relevance
“…3). From the radio emission and applying the fundamental plane of accreting BHs, a BH mass of 9 × (10 3 − 10 4 ) was estimated by Webb et al (2012) and an upper limit of 2.8 × 10 6 M by Cseh et al (2015a). Cseh et al (2015a) suggested that the radio emission is Dopplerboosted and that HLX-1 could be an outlier on the fundamental plane.…”
Section: Ultraluminous X-ray Sourcesmentioning
confidence: 99%
“…3). From the radio emission and applying the fundamental plane of accreting BHs, a BH mass of 9 × (10 3 − 10 4 ) was estimated by Webb et al (2012) and an upper limit of 2.8 × 10 6 M by Cseh et al (2015a). Cseh et al (2015a) suggested that the radio emission is Dopplerboosted and that HLX-1 could be an outlier on the fundamental plane.…”
Section: Ultraluminous X-ray Sourcesmentioning
confidence: 99%
“…While the formation channel of IMBHs is unknown, there are a small number of proposed scenarios: (i) the direct collapse of massive first-generation, lowmetallicity Population III stars [57][58][59][60], (ii) runaway mergers of massive main sequence stars in dense stellar clusters [61][62][63][64][65], (iii) the accretion of residual gas onto stellar-mass black holes [66], and (iv) chemically homogeneous evolution [67]. 6 It has been suggested that the most likely locations to find IMBHs are at the centers of GCs [68][69][70][71][72][73][74][75][76][77][78][79][80]. It follows that these are also the most likely places to find IMBHBs.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…In the microquasar GRS 1915+105, often compared to ULXs for its peak luminosity, steady jets are present during the hard so-called "plateau" state and ejection events during state changes (Mirabel and Rodríguez 1994;. Jets are associated with HLXs during state transitions, and this is considered evidence of the sub-Eddington regime, and so of their nature as IMBH (Cseh et al 2015a;Mezcua et al 2015). Only one sULXs, Holmberg II X-1, has been Fig.…”
Section: Jets and Outflowsmentioning
confidence: 99%